In vitro efficiency of teat disinfectants with organic matter against Staphylococcus aureus isolated from cows with mastitis - Talita Oliveira Maciel Fontes; Adriano França da Cunha; Mariana Costa Fausto; Fernando Nogueira de Souza; Mônica Maria Oliveira Pinho Cerqueira (Acta Scientiarum. Animal Sciences, 2024)
Four strains of Staphylococcus aureus isolated from cows with mastitis were assessed as to in vitro sensitivity to four commercial disinfectants (chlorine, polvidone-iodine, chlorhexidine, and lactic acid) used in teat pre- and post-dipping, in the presence and absence of organic matter. The concentration of the disinfectants was determined in accordance with the Brazilian Pharmacopoeia. Four isolates identified as S. aureus from cows diagnosed with subclinical mastitis were subjected to susceptibility testing against disinfectants through an absorbance evaluation at 600 nm on a spectrophotometer. Exposure times (15”, 30”, 60” and 90”) were clocked, and streaking was performed in Brain Heart Infusion (BHI) medium. The iodine sample presented a lower concentration (1.9%) than that given by the manufacturer (2.5%). There was greater (p < 0.05) in vitro disinfectant activity for chlorhexidine and chlorine, with and without organic matter. However, inhibition by organic matter occurred more intensely in the iodine disinfectant (99.0%). The inhibition percentage of S. aureus against iodine and lactic acid at 15, 30, 60 and 90 s was numerically lower than against chlorhexidine and chlorine, regardless of organic matter. Therefore, chlorhexidine and chlorine have greater inhibitory activity against S. aureus, both with and without organic matter.